Extracellular vesicles in blood: are they viable as diagnostic and predictive tools in breast cancer? - O'Driscoll, Lorraine (My University, 2020)
Extracellular vesicles (EVs), often described as mini-maps of their cells of origin, are found in the bloodstream and can be rich sources of cargo released from cancer cells. As such, they could be collected through minimally invasive methods and potentially used as biomarkers. However, the relatively complicated methodologies that separate the purest EVs are the least likely to be translated to the clinic, whereas simpler methods are non-selective for EVs. Notwithstanding this, research is underway to identify blood-based EV-associated diagnostic and predictive biomarkers for breast cancer. There is reason to be optimistic that some approaches will yield useful biomarkers. Thus, further studies with larger cohorts of appropriate samples are warranted.
Keywords: Cancer; BREAST CANCER; CANCER; Extracellular Vesicles; Extracellular vesicles (EVs); exosomes; Health